Cancer-associated fibroblasts, and clinicopathological characteristics and prognosis of gastric cancer: A systematic review and meta-analysis - Wei, Jinwu; Wang, Mingxia; Li, Guixiang (Frontiers in Oncology, 2023)
Objective: To systematically evaluate the relationship between cancer-associated fibroblasts (CAFs) and clinicopathological characteristics and prognosis of gastric cancer, so as to provide new directions and clinical evidence for the diagnosis and treatment of this disease. Methods: We searched PubMed, Embase, Web of Science, and The Cochrane Library to identify studies on the correlation between tumor-associated fibroblasts and the diagnosis and prognosis of gastric cancer. Two researchers screened the literature independently to extract data, evaluated the quality of the included studies, and used the Review Manager 5.4 software to perform a meta-analysis. Results: A total of 14 studies involving a total of 2,703 patients were included. The meta-analysis results showed that high expression of CAFs was associated with stage III–IV gastric cancer (relative risk ratio [RR]=1.59; 95% confidence interval [CI]: [1.24–2.04]; P=0.0003), lymph node metastasis (RR=1.51; 95% CI: [1.23–1.87]; P=0.0001), serosal infiltration (RR=1.56, 95% CI: [1.24–1.95]; P=0.0001), diffuse and mixed types in Lauren classification (RR=1.43; 95% CI: [1.18–1.74]; P=0.0003), vascular invasion (RR=1.99; 95% CI: [1.26–3.14]; P=0.003), and overall survival (hazard ratio [HR]=1.38; 95% CI: [1.22–1.56]; P<0.00001). However, the high expression of CAFs was not significantly correlated with poorly differentiated gastric cancer (RR=1.03; 95% CI: [0.96–1.10]; P=0.45) and gastric cancer with tumor diameter >5 cm (RR=1.34; 95% CI: [0.98–1.83]; P=0.07). Conclusion: The findings of this meta-analysis demonstrated that high expression of CAFs is closely associated with the traditional pathological indicators related to poor prognosis in gastric cancer, and is a valuable prognostic factor in this setting.